Hydrodifluoromethylation of Alkenes with Difluoroacetic Acid. (23rd May 2019) - Meyer, Claudio F.; Hell, Sandrine M.; Misale, Antonio; Trabanco, Andrés A.; Gouverneur, Véronique
Abstract: A facile method for the regioselective hydrodifluoromethylation of alkenes is reported using difluoroacetic acid and phenyliodine(III) diacetate in tetrahydrofuran under visible‐light activation. This metal‐free approach stands out as it uses inexpensive reagents, does not require a photocatalyst, and displays broad functional group tolerance. The procedure is also operationally simple and scalable, and provides access in one step to high‐value building blocks for application in medicinal chemistry. Abstract : Die Hydrodifluormethylierung terminaler Alkene gelang mit einem Überschuss an Difluoressigsäure und Phenyliod(III)diacetat in Tetrahydrofuran bei Bestrahlung mit sichtbarem Licht ( λ =450 nm). Diese praktikable Methode vereinfacht die Synthese biorelevanter Bausteine, deren Herstellung durch Deoxyfluorierung mehrere Stufen benötigen würde.